The button box a daughter's loving memoir of Mrs. George S. Patton - Totten, Ruth Ellen Patton, 1915- (University of Missouri Press, 2005)
"Memoir of Beatrice Ayer Patton (1886-1953), the wife of General George S. Patton, Jr. The book covers Beatrice's life from her youth in New England until her death, with an emphasis on her years of marriage to George Patton"--Provided by publisher.